2013
DOI: 10.2169/internalmedicine.52.9102
|View full text |Cite
|
Sign up to set email alerts
|

Familial Mediterranean Fever Occurring in an Elderly Japanese Woman with Recent-onset Rheumatoid Arthritis

Abstract: A 60-year-old woman with a two-year history of rheumatoid arthritis (RA) developed recurrent two- to three-day attacks of fever (>38 °C) accompanied by monoarthritis of the right hip joint. The first attack occurred two months after beginning anti-tumor necrosis factor-α therapy. Since a diagnosis of infectious arthritis was suspected, the therapy was discontinued. Thereafter, the patient repeated similar episodes; however, oral colchicine effectively controlled the attacks. The patient was diagnosed to have f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…According to previous studies on the correlation between the MEFV genotype and the severity of disease in FMF, mutations in exon 2 (E148Q, E148Q/L110P) are associated with milder clinical features . Case 2 was diagnosed with FMF because of recurring high‐grade fever and the change in arthritis location; however, the patient had no serositis, and in her febrile attacks, the fever was sometimes only low grade and ended within a few hours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to previous studies on the correlation between the MEFV genotype and the severity of disease in FMF, mutations in exon 2 (E148Q, E148Q/L110P) are associated with milder clinical features . Case 2 was diagnosed with FMF because of recurring high‐grade fever and the change in arthritis location; however, the patient had no serositis, and in her febrile attacks, the fever was sometimes only low grade and ended within a few hours.…”
Section: Discussionmentioning
confidence: 99%
“…1 Although the age of onset among Japanese FMF patients tends to be much later than that in the Mediterranean population, in only 6% of all reported cases did onset occur after 50 years of age. [2][3][4] Almost all FMF patients carry a mutation in the MEFV gene which is known to be associated with rheumatic diseases [5][6][7][8][9][10] ; however, the coexistence of FMF with rheumatoid arthritis (RA) is quite rare, 11,12 although it has been suggested that there may be an association between a mutation of the MEFV gene in exon 2 and the severity of RA. 13 Here we describe two cases of RA patients diagnosed with FMF and carrying a mutation of the MEFV gene in exon 2.…”
Section: Introductionmentioning
confidence: 99%
“…Inoue et al recently reported the case of an FMF patient with onset at 66 years of age (5), and Mori et al reported an FMF patient with onset at 60 years of age (6). To the best of our knowledge, two of the present cases are the oldest reported FMF patients in Japan (5)(6)(7)(8). According to the nationwide study of FMF in Japan, the mean age at the time of diagnosis was 28.7±18.5 years, and the mean age at the onset of symptoms was 19.6±15.3 years (2).…”
Section: Discussionmentioning
confidence: 99%
“…There is only one case report from Japan reporting a patient with fever, rash, and polyarthralgia who was put on TCZ with a probable diagnosis of RA with good response. The diagnosis was switched to FMF when the patient was found to carry one copy of M694I [ 96 ].…”
Section: Anti-il-6 Treatmentmentioning
confidence: 99%